Trachoma in remote Indigenous Australia: a review and public health perspective - Johanna M. Warren; Alexander L. Birrell (Elsevier, 2016)
Abstract Objectives: Trachoma remains a major health concern in many remote Indigenous Australian communities, despite behaviour‐modifying and biomedical strategies. This review aims to examine the social epidemiology of trachoma in remote Indigenous communities and identify practical, sustainable strategies to alter the social determinants of the disease. Methods: A systematic search and critical review explored the proximal, intermediate and distal determinants of trachoma. The impact of swimming pools in remote Indigenous communities on trachoma and other infectious diseases was further examined. Results: Having a clean face was found to be protective for trachoma, but face‐washing education programs have produced no significant benefits. Sanitation infrastructure in a community was the key determinant of facial cleanliness. Installation of swimming pools in remote Indigenous communities has been demonstrated to reduce the prevalence of several common childhood infections. However, minimal research has explored the impact of pools on trachoma rates. Conclusions: The locally supported construction of pools in remote Indigenous communities may contribute to a decline in trachoma. A prospective, controlled trial is needed to test this hypothesis in endemic communities. Implications: If validated by a well‐designed study, pool construction may provide a much sought‐after practical government strategy to combat trachoma in remote Indigenous communities.